Early Vascular Damage in Young Women with DM-1 and Its Relation to Anti-Müllerian Hormone: A Cross-Sectional Study - Annelien C. de Kat; Hendrik Gremmels; Marianne C. Verhaar; Frank J. M. Broekmans; Felicia Yarde (International Journal of Endocrinology)
Vascular function is suggested to be associated with ovarian reserve, but the relationship with microvascular function has never been studied. In this cross-sectional pilot study, the relationship of microvascular damage markers with AMH was studied in premenopausal women. Twenty-two regularly cycling women with type 1 diabetes (DM-1) and a reference group of 20 healthy regularly cycling women were included, from whom blood was drawn in the early follicular phase of the menstrual cycle. The main outcome was the correlation between circulating progenitor cells (CPCs), markers for early vascular damage, and AMH, a marker for ovarian reserve. Secondary endpoints for early vascular impairment were circulating angiogenic cells and additional biomarkers. Median AMH levels were 2.2 µg/L [1.2–3.5] in the DM-1 group and 2.1 µg/L [0.85–3.8] in the reference group. CPCs were significantly decreased in women with DM-1; 1204±537 CD34+/CD45dim cells were counted in the DM-1 group, compared to 2264±1124 in the reference group. CPCs and other markers of early vascular damage were not correlated with AMH levels in a multivariable analysis. These results underscore previous findings of early vascular damage in DM-1 and suggest that there may not be a relationship between vascular function and ovarian reserve. Trial Registration. This trial is registered with Clinicaltrials.gov NCT01665716.